Pathological findings in a patient with dermatomyositis associated with severe dysphagia - TAKEUCHI, Satoshi; TAYAMA, Niro; YAMAMOTO, Miyuki; NITO, Takaharu; ADACHI, Nodoka; MISAKI, Yoshikata (OTOLOGIA FUKUOKA, 2004)
Pathological findings in a patient with dermatomyositis associated with severe dysphagia are presented. Biopsy specimens from several neck muscles of a 70-year-old female patient who under went cricopharyngeal myotomy were obtained. The thyropharyngeal, cricopharyngeal and esophag eal muscles were atrophied and fibrous, while the platysma, sternocleidomastoid, omohyoid, and sternothyroid muscles were normal. The atrophy and fibrosis of the cricopharyngeal muscle were the findings common to those previously reported. At present, the cause of the atrophy and fibro sis specially of the pharyngeal constrictor muscles or esophageal muscles remains unclarified and therefore requires further examinations.